Measurement of water vapor line strengths in the 1.4–2.7 µm range by tunable diode laser absorption spectroscopy. (November 2015) - Pogány, Andrea; Klein, Alexander; Ebert, Volker
Abstract: Line strengths of nine water vapor absorption lines in the wavelength range between 1.37 and 2.71 µm with line strengths of 10 –23 –10 –20 cm/molecule have been measured using direct tunable diode laser absorption spectroscopy (dTDLAS). Four different light sources were used: three distributed feedback (DFB) diode lasers with wavelengths of 1.37 µm, 2.55 µm and 2.71 µm for measuring one application-specifically selected absorption line with each laser, and a vertical-cavity surface-emitting laser (VCSEL) radiating around 1.39 µm for the measurement of six further absorption lines. Despite the different light sources and line strengths, a uniform measurement and data evaluation method was developed and applied to all lines, and the experimental set-up was kept as similar as possible. This allows a thorough and uniform uncertainty analysis and evaluation of the contributions of the individual experimental parameters to the uncertainty of the derived line strengths. A comprehensive and transparent uncertainty analysis is given for the measurements. Uncertainties of our measured line strengths are in the 1.1–2.5% range ( k =2, 95% confidence level). Our measured line strength values agree well with line strengths in the HITRAN 2012 database and other literature sources, we realized lower uncertainties up to a factor of 5–10. Highlights: Accurate line strength measurement of nine NIR water vapor lines. dTDLAS set-up using a single pass cell and different diode lasers (DFB and VCSEL). Detailed uncertainty assessment, combined expanded uncertainty of 1.1–2.5% (95% conf. interval). Results compare well to literature values, but show lower uncertainty.